Features of the definition of some legal terms in the civil legislation of the Republic of Kazakhstan and the Republic of Turkey - Akimzhanova, M.T.; Assetova, G.B.; Muratova, A.K. (Bulletin of the Karaganda University “Law Series”, 2023)
The article is devoted to a comparative legal analysis of the peculiarities of the use of certain legal terms in the civil legal acts of the Republic of Kazakhstan and the Republic of Turkey. As a result of the analysis, certain patterns were identified in the development of legal terminology in the civil law norms and acts. This can serve as a basis for creating a holistic picture of the formation of a legal language in the process of formation of the domestic civil law of the Republic of Kazakhstan. The study of the problems that are associated with the functioning of legal terminology in the modern civil legislation provides grounds for a comprehensive understanding of ways to improve the domestic regulatory space. The authors substantiated the conclusions and recommendations that have a theoretical and practical significance, supported by specific examples, and aimed at improving the quality of the texts of the civil legal normative acts of the Republic of Kazakhstan. Theoretical conclusions and developed practical recommendations can be used in the development of general rules of legal technique, improvement of the law of the Republic of Kazakhstan “On Legal Acts”, as well as to improve rule-making and law enforcement practice in activities, which are associated with the linguistic examination of bills in the state language. The authors have proposed the introduction of the commonly used legal terminology, which contains ordered, generally accepted, uniform and properly formalized legal terms. During the study, methods of scientific knowledge: synthesis, analysis,induction, deduction, in addition, comparative legal, systemic, logical methods have been applied.